2005
DOI: 10.1111/j.1464-5491.2005.01677.x
|View full text |Cite
|
Sign up to set email alerts
|

The perils of procrastination: effects of early vs. delayed detection and treatment of incipient Charcot fracture

Abstract: Early detection of incipient Charcot foot is facilitated by imaging techniques other than plain X-rays. Immediate off-loading of incipient Charcot foot appears to minimize fractures and incapacitating deformities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
159
1
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(178 citation statements)
references
References 13 publications
8
159
1
10
Order By: Relevance
“…A possible explanation for the long off-loading periods (and high recurrence) might be the time elapsed from the first sign of CA to the time of off-loading, as reported by Kimmerle (Kimmerle & Chantelau, 2007). Patients with the shortest period between onset and treatment had the best outcome (Chantelau, 2005). It might also be hypothesised that the introduction and popularization of highly sensible scanning methods as bone scintigrams, PET CT and MRI, which are useful in early diagnosis and precise mapping of the lesions might also lead to inadequate postponing of weight load if used in monitoring.…”
Section: Discussionmentioning
confidence: 87%
“…A possible explanation for the long off-loading periods (and high recurrence) might be the time elapsed from the first sign of CA to the time of off-loading, as reported by Kimmerle (Kimmerle & Chantelau, 2007). Patients with the shortest period between onset and treatment had the best outcome (Chantelau, 2005). It might also be hypothesised that the introduction and popularization of highly sensible scanning methods as bone scintigrams, PET CT and MRI, which are useful in early diagnosis and precise mapping of the lesions might also lead to inadequate postponing of weight load if used in monitoring.…”
Section: Discussionmentioning
confidence: 87%
“…All patients underwent endovascular revascularization, in addition to surgical reconstruction, achieving a limb salvage rate of 90%. Chantelau (22) reported a PAD rate of 12.5% in a study assessing the early diagnosis of CN; however, he did not define the method by which PAD was diagnosed. Sohn et al (23) reported that PAD was present in 26.9% of US military veterans with CN.…”
Section: Discussionmentioning
confidence: 96%
“…The reported rates of PAD in patients with CN have ranged from 4.4% to 35.4% (21)(22)(23)(24). Most of these studies did not specifically evaluate the prevalence of PAD but, rather, reported on a series of patients with CN (21)(22)(23). The precise definition of PAD was not well defined in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nonoperative measures such as total contact casting are regarded as treatment of choice for a majority of patients if the treatment is likely to provide a plantigrade foot without major bony destruction and deformities [6,7,31]. According to some series, however, 40% to 50% of these patients may have secondary surgery due to recurrent ulcers or residual deformity [3,5,12,23,29].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, unstable deformities in these frequently obese patients are difficult to brace with a high inherent risk of ulceration in the insensate feet [19,21]. Late institution of immobilization and unloading runs a high risk of permanent deformity after healing [6,14]. An underlying fixed deformity or osseous prominence is one of the main reasons for recurrence of ulceration [35].…”
Section: Introductionmentioning
confidence: 99%